CO-evaluation of Immunhistochemical PD-L1 and FOXP3 Expressions in Breast Cancer - Özge KAYA KORKMAZ; Gülden DİNİZ; Gülen GÜL; Ceren SAYAR (Forbes Tıp Dergisi, 2023)
Objective: Breast cancer is the most common cancer among women and is the second most frequent cause of cancer-related deaths worldwide. The aim of this study was to determine the prognostic values of PD-L1 expression in breast cancers and to detect the presence of FOXP3-positive Treg cells in the tumor microenvironment. Methods: This study included 210 females with breast cancer who had been histopathologically diagnosed in our hospital between 2011 and 2014. Results: In this series, the mean age of the patients was 55.46 (12.5) years and they were followed up for a mean period of 61.9 (20.6) months. In only 6 cases (2.9%), there were weak membranous expressions of PD-L1 in tumor cells. However, PD-L1-positive inflammatory cells were seen in 15 tumors (7.1%). There was no significant relationship between PD-L1 expression and survival (p>0.05). In 14 (6.7%) cases, there were FOXP3-positive lymphocytes. The range of FOXP3-positive cells was between 1 and 30/HPF. There was no statistically significant association between survival times and the presence of Tregs (p>0.05). Conclusion: In this study, no relation was found between PD-L1 positivity and molecular subtypes, histological grade, stage, and hormone receptor status of the breast tumor. There was no statistically significant relationship between FOXP3 and PD-L1 molecule and overall survival. We found a minimal positive effect of the presence of Treg inflammatory cells on survival. However, this relationship could not be proved by statistical analyzes